Medical aspects of competitive diving - Zimmermann, W. (coachesinfo.com, 2008)
Starting in 1985, the author has compiled a bibliography on competitive diving with 3300 references to books and articles. Many of the books and articles have been collected via university libraries, colleagues and the internet. The complete list of titles is directly accessible for everybody through www.springschool.nl